The gendered double standard of accumulating and utilizing erotic capital : How aesthetics affects possibilities in the labor market? - Mattila, Kukka (My University, 2024)
Visual consumer culture is one of the most influential descriptions of modern Western society, alongside the emergence of media and market societies. Within consumer culture, physical appearance, and body, and its image are of the utmost importance. The culture entails an underlying assumption that people should attend to their bodies and their body image in an instrumental manner, since status and social acceptability depend heavily on attractiveness. The construct of appearance is exclusive and narrow and has a substantial gender dimension. Girls and women are socialized by cultural norms to see beauty as a feminine mandate and attaining it as a feminine responsibility. Furthermore, women tend to have significantly more aesthetic and erotic capital, compared to men. Despite women’s higher erotic capital, attractiveness seems to yield disadvantages for women. The given scrutiny and disadvantages linked with aesthetics seem to be greater for women and their bodies. The norms regulating the accumulation and utilization of erotic capital affect outcomes in the labor market. While attractiveness has gained an increased interest among researchers it has mostly been studied from the viewpoint of aesthetic capital, overlooking erotic capital. The lack of research could be due to the patriarchal bias in social and economic sciences, since erotic capital is noted to be a highly feminine capital. Previous research has majorly overlooked the societal norms regulating the accumulation and utilization of aesthetic capital between women and men. Moreover, the gendered double standard that prevails, especially in the labor market, has been greatly overlooked. This research aimed to answer this research gap by gaining an understanding of the gendered double standard of accumulating and utilizing erotic capital. The empirical study in the thesis was conducted as qualitative research, with the purpose to understand the perceptions of the interviewees, and whether there is a gendered double standard on erotic capital in the labor market. Furthermore, according to the interviewee’s experiences, the effects of gender and physical attractiveness on labor market outcomes for both genders are examined. Human action is embedded with various intentions and meanings, and the qualitative method is very well suited to examining these kinds of phenomena. The research was conducted by using a semi-structured theme interview as a data collection method. The themes for the interviews were predetermined and the set questions acted as structure and support for the interviewers in the moment of the interviews. The study results indicated there to be an evident and significant gendered double standard of accumulation and utilization of erotic capital that affects labor market outcomes. The central findings underlined the significance of erotic capital as its own capital. The utilization of appearance seemed to go so much further and to be far more multidimensional beyond beauty and looks. Furthermore, erotic capital was evidently linked with gender and mediated by age and weight. Attractiveness was found to be linked with higher rewards, while less attractive looks were linked with disadvantages and penalties. However, it seems that when women perform in the expected manner of the societal norms, as in accumulating and utilizing their attractiveness, it does not seem to benefit them. On the contrary, in the context of the labor market, especially in more male-dominated fields and positions, women seem to be penalized for it.

Visuaalinen kulutuskulttuuri, median läpimurron ja kulutusyhteiskunnan nousun ohella, leimaa merkittävästi modernia länsimaista yhteiskuntaa. Kulutuskulttuurissa ulkonäöllä, etenkin keholla ja kehonkuvalla, on keskeinen merkitys. Kulttuuriin on sisäänrakennettuna välineellinen näkemys kehosta ja kehonkuvasta keinoina saavuttaa sosiaalista hyväksyntää ja yhteiskunnallista statusta, sillä viehätysvoimalla katsotaan olevan niihin suuri vaikutus. Vallitsevien normien sisäpuolelle mahtuva käsitys hyväksyttävästä ulkonäöstä on paitsi kapea ja poissulkeva, myös erittäin sukupuolittunut. Kulttuuriset normit opettavat tytöt ja naiset näkemään kauneuden feminiinisenä pakkona, ja sen ylläpitämisen naiseuteen liittyvänä vastuuna. Naisten on katsottu omaavan huomattavasti enemmän esteettistä ja eroottista pääomaa miehiin verrattuna. Huolimatta naisten suuremmasta eroottisesta pääomasta, ulkonäköön kohdistuvien haittapuolien ja paheksunnan on havaittu kohdistuvan eniten naisiin ja heidän kehoihinsa. Eroottisen pääoman kerryttämistä ja hyödyntämistä määrittävät normit vaikuttavat myös työmarkkinoilla. Tieteellinen tutkimus on yhä enemmissä määrin kohdistunut ulkonäköön, mutta suurimmaksi osaksi vain esteettisen, ei eroottisen pääoman näkökulmasta. Eroottiseen pääomaan liittyvän tutkimustiedon vähäisyyden voidaan katsoa johtuvan patriarkaattiin liittyvästä puolueellisuudesta sosiaali- ja taloustieteissä, liittyen eroottisen pääoman feminiiniseen luonteeseen. Aiempi tutkimus on jättänyt pitkälti huomiotta myös esteettisen pääoman sukupuolittunutta kerryttämistä ja hyödyntämistä koskevat normit. Aihealueen tutkimusperinne on puutteellista etenkin työmarkkinoiden kontekstissa. Tämän tutkielman tavoitteena onkin vastata kyseiseen tutkimusaukkoon tarkastelemalla ja ymmärtämällä eroottisen pääoman kerryttämiseen ja hyödyntämiseen liittyvää sukupuolittunutta kaksoisstandardia. Tutkimus toteutettiin käyttämällä kvalitatiivista tutkimusotetta, tarkoituksena ymmärtää haastateltavien näkemyksiä, selvittää, onko niiden kautta havaittavissa työmarkkinoilla eroottiseen pääomaan liittyvää kaksoisstandardia. Lisäksi tarkastelun kohteena olivat haastateltavien kokemukset sukupuolen ja ulkonäön vaikutuksista työmarkkinoilla. Ihmisen toiminta sisältää useita eri tarkoituksia ja merkityksiä, joiden tarkasteluun kvalitatiivisen tutkimusotteen voidaan katsoa soveltuvan. Tutkimuksen aineistonkeruumenetelmänä olivat puolistrukturoidut teemahaastattelut. Haastatteluteemat olivat ennalta määriteltyjä, ja käytetty kysymyspatteristo toimi haastattelujen runkona ja keskustelujen tukena. Tutkimuksen tulokset viittasivat ilmeiseen ja merkittävään sukupuolittuneeseen kaksoisstandardiin työmarkkinoilla, liittyen eroottisen pääoman kerryttämiseen ja hyödyntämiseen. Havainnot vahvistivat eroottisen pääoman roolia omana pääomanaan, sillä ulkonäön hyödyntämisen havaittiin olevan merkittävästi laajempi ja monisyisempi kokonaisuus, kuin vain esteettisyyteen liittyvät ihmisen kauneus ja ulkonäkö. Lisäksi tuloksista oli havaittavissa sukupuolen, iän ja painon merkittävä yhteys eroottiseen pääomaan. Viehättävyyden nähtiin olevan yhteydessä korkeampiin hyötyihin, kun taas vähäisempään eroottiseen pääomaan liitettiin vahvasti haittapuolia ja rangaistuksia. Tutkimustulokset osoittavat kuitenkin, että vaikka naisilta odotetaan yhteiskunnan normien mukaista eroottisen pääoman kerryttämistä ja hyödyntämistä, siitä ei kuitenkaan seuraa naisille hyötyjä. Työmarkkinoiden kontekstissa, etenkin miesvaltaisilla aloilla ja positioissa ulkonäön hyödyntämisellä nähtiin olevan naisille epäedullinen vaikutus.
Keywords: aesthetic capital, erotic capital, gendered double standard, accumulation and utilization of erotic capital, labor market